The Influence of Self-Competency and Extraversion on the Performance of School Supervisors - Safrijal Safrijal; Sumarjo Sumarjo; Basri Basri (STAI Hubbulwathan Duri, 2023)
School supervisors play a vital role and have the responsibility for overseeing the learning process. This study aims to ascertain the impact of self-competence and extraversion on the performance of school supervisors. This study is a quantitative research study that utilises an ex-post facto research design. Ex-post facto research focuses on testing ideas by manipulating variables. The acquired data consisted of responses provided by the madrasa supervisor in response to the posed inquiries. The sample for this study consisted of 47 school supervisors in Pidie District. The data collection instrument utilised was a Likert scale questionnaire. Utilising design path analysis to employ data analysis methodologies. The findings of this study revealed that the impact of self-competence on extraversion was 0.294, which accounts for 29.4% of the variance. Similarly, the influence of self-competence on teacher performance was 0.309, representing 30.9% of the variance. Additionally, extraversion was found to have an influence of 0.412, explaining 41.2% of the variance in teacher performance. Conducting an evaluation of supervisors is essential to analyse their work and categorise the accomplishments of school supervisors, as indicated by the findings of this study.